ANALISIS PERBANDINGAN EFISIENSI BIAYA PENGGUNAAN LINUX CLEAROS DAN MIKROTIK UNTUK KEBUTUHAN SOHO - Putu Veda Andreyana; I Made Sunia Raharja; I Putu Agus Eka Pratama (J-ICON : Jurnal Komputer dan Informatika, 2022)
Currently, various sectors of life and organizations require the availability of computer networks and the internet to be able to provide faster and optimal services, one of which is the Small Office Home Office (SOHO). Internet access requires management so that the internet network can be allocated according to the needs of each field and requires cost calculations according to the ability of the organization. Linux ClearOS and Mikrotik are two operating system platforms commonly used for network management, including SOHO. The test was conducted in the form of a comparison between ClearOS Linux and Mikrotik in terms of cost, basic network capabilities (bandwidth manager, wifi, proxy, load balancing, user management), availability of security features, and additional device requirements. The test results show that for the same needs on SOHO, Linux ClearOS has advantages in terms of lower costs and complete features, so it is more recommended than Mikrotik